Investigation of the effects of Afyonkarahisar Region hot springs water on blood calcium and some hormon levels in experimentally-created osteoporosis in rats - Bülent Elitok; Tolgahan Saygin; Yavuz Ulusoy; Bahadir Kilinç (Ветеринария сегодня)
Today, one of the most common non-communicable diseases, which, according the World Health Organization experts, dominates the structure of human morbidity and mortality is osteoporosis. The aim of this study was to determine the effect of water from the hot springs of the Afyonkarahisar region on the calcium content and the levels of certain hormones in the blood of rats with experimentally induced osteoporosis. 25 female albino rats of the same age were used in the experiment. Ovaries were removed from all animals under anesthesia with ketamine (200 mg/kg) and xylazine (10 mg/kg), after which they were divided into two groups: control (10 animals) and experimental (15 animals). The animals of the control group were given tap water twice a day through an orogastric tube and they were bathed in it for 15 minutes at the same time, the water temperature was (35 ± 2) °C. The animals of the experimental group were given fresh water from the Süreyya I hot spring using the same method. Blood clinical, hematological and biochemical parameters were measured prior to the study, as well as on day 1, 7, 14, and 21 after the ovariectomy operation. The ovariectomy demonstrated inconsistence of the tested blood parameters with the standard ones. In the course of the treatment, by day 21 of the experiment, the parameters normalized, and the most noticeable changes were observed in the rats of the experimental group (p < 0.05). The results of the work performed showed that Süreyya I hot spring water contributed to a significant improvement in the clinical, hematological and biochemical blood parameters in rats with osteoporosis, therefore, it can be used for prevention and treatment of this disease in combination with other types of treatment.